Endemic Lineages of Batrachochytrium dendrobatidis Are Associated With Reduced Chytridiomycosis-Induced Mortality in Amphibians: Evidence From a Meta-Analysis of Experimental Infection Studies - Belasen, Anat M.; Russell, Imani D.; Zamudio, Kelly R.; Bletz, Molly C. (Frontiers in Veterinary Science, 2022)
Emerging infectious wildlife diseases have caused devastating declines, particularly when pathogens are introduced in naïve host populations. The outcome of disease emergence in any population will be dictated by a series of factors including pathogen virulence, host susceptibility, and prior coevolutionary opportunity between hosts and pathogens. Historical coevolution can lead to lowered pathogen virulence and/or increased host resistance that allows stable persistence of both host and pathogen. In some cases, adaptive coevolution can occur on relatively short time scales following introduction of a novel pathogen. Here, we performed a meta-analysis of experimental infection studies to examine whether the potential for long- or short-term coevolution determines the outcome of amphibian chytridiomycosis infections. We hypothesized that the opportunity for host-pathogen coevolution leads to reduced susceptibility to lethal chytridiomycosis in amphibian hosts infected with Batrachochytrium dendrobatidis (Bd). We performed a meta-analysis of multi-strain Bd infection experiments to test whether: (1) amphibians exhibit lower mortality rates when infected with strains belonging to endemic Bd lineages relative to the global panzootic lineage (Bd-GPL), hypothetically owing to long coevolutionary histories between endemic Bd lineages and their amphibian hosts; and (2) amphibians exhibit lower mortality rates when infected with local Bd-GPL strains compared with non-local Bd-GPL strains, hypothetically owing to recent selection for tolerance or resistance to local Bd-GPL strains. We found that in a majority of cases, amphibians in endemic Bd treatments experienced reduced mortality relative to those in Bd-GPL treatments. However, we detected no overall difference in amphibian mortality between local and non-local Bd-GPL treatments. Taken together, our results suggest that long-term historical coexistence is associated with less severe disease, potentially due to coevolutionary selection for hypovirulence in endemic Bd lineages.